'All about Eve': Mothers, Masculinities and the 2011 UK Riots. (15th May 2013) - Ashe, Fidelma
<x xml:space="preserve">Abstract</x> The riots that erupted in English cities in August 2011 were provoked by a complex mix of socio‐economic factors. Sidelining structural explanations for the civil disorder, conservative commentators argued that dysfunctional families had caused the riots. Reinforcing traditional connections between criminality, the family and welfare, conservatives contended that the absence of fathers in lone mother‐headed families explained both the dynamics of the civil disorder and the aggressive behaviour of some of the young men involved. Such claims located both the causes of the riots and solutions to expressions of violent masculinities in the familial sphere. Employing the framework of critical studies of men and masculinities this article interrogates these narratives and maps their depoliticising effects. Additionally, it exposes how the effects of a range of social problems were projected on to poor, lone mothers, reinforcing a range of regulatory narratives and practices that target this social group.